2004
DOI: 10.1158/1078-0432.ccr-0597-3
|View full text |Cite
|
Sign up to set email alerts
|

KIT (CD117)-Positive Breast Cancers Are Infrequent and Lack KIT Gene Mutations

Abstract: Purpose: KIT (CD117) is a transmembrane tyrosine kinase representing a target for STI571 (Glivec) therapy. Some KIT-overexpressing solid tumors have responded favorably to STI571, potentially because of the presence of KIT-activating mutations.Experimental Design: To investigate the epidemiology of KIT overexpression and mutations, we investigated a series of 1654 breast cancers. All tumors were analyzed by immunohistochemistry in a tissue microarray format.Results: KIT expression was always present in normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(56 citation statements)
references
References 53 publications
4
51
0
1
Order By: Relevance
“…The striking link of high Cdc7 expression rate with medullary or medullary-like breast carcinomas constitutes another argument in favor of a biologic uniqueness of this rare subtype of breast cancer. Expression of other relevant proteins like KIT, cytokeratin 5/6, p63, or EGFR has been associated with the medullary phenotype of breast cancer before [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The striking link of high Cdc7 expression rate with medullary or medullary-like breast carcinomas constitutes another argument in favor of a biologic uniqueness of this rare subtype of breast cancer. Expression of other relevant proteins like KIT, cytokeratin 5/6, p63, or EGFR has been associated with the medullary phenotype of breast cancer before [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Soft tissue tumours other than GIST and germinal cell tumours are rarely KIT-positive [16]. KIT expression has also been reported in melanocytic tumours [17] and carcinomas of the lung [18], ovarium [19], breast [20], colon [21], prostate [22] and kidney [23].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the presence of activating mutations in specific exons of c-kit are associated with a greater response to imatinib therapy in KIT-positive GISTs [22]. Most recently, the results of a large retrospective study have shown that of 1654 cases of breast cancer tested for KIT expression by IHC on archived tissues, only 43 cases (2.6%) had detectable protein; 10 of 10 KIT-positive cases also tested negative for known activating gene mutations [23]. Hence, it seems unlikely that drugs targeting this pathway would be of major clinical importance in breast cancer.…”
Section: Discussionmentioning
confidence: 99%